The probiotic Enterococcus faecium modifies the intestinal morphometric parameters in weaning piglets (2016)
Global trends for animal production have seen a decrease in the use of antimicrobial compounds in feed, generating the need to implement new nutritional strategies that stimulate growth and promote intestinal health. This study aimed to determine whether the addition of E. faecium in drinking water improves intestinal morphometric parameters in post- weaning pigs compared with the probiotics strains L. acidophilus and L. casei on days 1 (21 days of age), 15 and 30 postweaning. The small intestine was completely removed to evaluate the morphometric parameters (length and width of villi and crypts) in the different intestinal segments (duodenum, jejunum, and ileum). They were fed for 30 days with two diets: commercial diet with or without antibiotics. The different probiotics, L. acidophillus, L. casei and E. faecium, were administered in the drinking water of the animals that consumed the commercial diet without antibiotics. A randomized block design in split-plot arrangement was used. There was a significant increase (P0.01) in the width and length of villi, and a decrease (P0.01) in the values obtained for the width and depth of crypts in the animals that consumed E .faecium, as compared to those that consumed the diet with addition of antibiotics. The use of probiotics, especially E. faecium, is a nutritional treatment strategy when antimicrobial compound are used, improving the intestinal morphometric parameters and, at the same time, the digestive and productive parameters of the animals. Work is in progress to investigate the effects of probiotic supplementation on the mofication of gut microbiota of post-weaning piglets